Photoluminescence behaviour of a stimuli responsive Schiff base: Aggregation induced emission and piezochromism - Yadav P.; Singh A.K.; Upadhyay C.; Singh V.P. (My University, 2025)
A naphthaldehyde based Schiff base, HMP has been synthesized by simple one-pot synthesis and characterized by IR, NMR and mass spectral techniques. HMP was non-emissive in acetonitrile, but its emission intensity was enhanced drastically (68 folds) upon addition of water, demonstrating typical aggregation induced emission (AIE) behaviour. Fluorescence quantum yield was increased drastically on aggregation from 0.3% (fw = 0%) to 8.1% (fw = 99%). Lifetime decay measurements were also performed in support of AIE property. Single crystal X-ray diffraction and DFT studies reveal that conformational transformation from benzenoid to quinonoid form induces restricted intramoleclar rotation (RIR) which contributes to AIE property. HMP was found to exhibit strong luminescence and piezochromism in solid state. Interestingly, dark yellow luminescence of crystalline HMP was changed to light green in response to grinding and a blue shift from 544 nm to 531 nm was observed. HMP exhibits good parent crystalline maintenance capability during grinding. Synthetic ease and reversible transformation of HMP are the key features to establish its application in pressjet printing and pressure sensing. © 2018 Elsevier Ltd